Hubungan antara Sukungan Sosial, Jenis Kelamin, dan Tingkat Pendidikan dengan Depresi dan Fungsi Kognitif Lanjut Suia dalam Komunitas Keagamaan - Jayadi, Tejo; The, Maria Meiwati Widagdo; Sooai, Christiane Marlene; Indonesia, Bunga Matahari; Agustina, Maria; Waskitaningtyas, Bernadeta Amaya (Atma Jaya Catholic University of Indonesia, 2024)
Introduction: Elderly individuals often experience psychosocial vulnerabilities that increase their risk for psychological disorders and are linked to cognitive impairments. This study explored how social support and demographic variables relate to the incidence of depression and cognitive decline among devout older adults. Methods: This cross-sectional observational study involved 125 senior participants from the Javanese Christian Church in Ambarrukma District of Yogyakarta. The research utilized demographic questionnaires, social support evaluations, surveys on religious attitudes, the Geriatric Depression Scale, and the MOCA-Ina tests. Data will undergo univariate and bivariate analyses and binary linear regression to evaluate odds ratios (OR), 95% confidence intervals (CI), and Pearson correlations between variables. Results: Elderly devout respondents (99.2%) who received good social support were more likely to experience no depression (47.9%) than those with poor social support (40.3%) (p=0.025; OR 0.182; 95% CI 0.038-0.873). The female gender suffered more from mild depression (p=0.021; OR 0.176; 95% CI 0.037-0.841) compared to men. Older adults with an education level of 7 years or more showed less mild cognitive impairment (p=0.044; OR 4.500; 95% CI 0.929-21.802). Conclusion: This study revealed that social support plays a role in modifying the incidence of depression in devout elderly individuals. The female gender suffered more from mild depression. Additionally, lower education levels were correlated with mild cognitive impairment. Further research with a more robust analysis with a larger sample size and consideration of other factors is necessary to confirm the causal relationships between social support and gender and depression.